A patient notification exercise for Mycobacterium chimaera infection associated with cardiac bypass surgery: the Welsh perspective. (December 2017) - Davies, L.; Stiff, R.; Davies, E.; Shankar, A.G.; Jenkins, S.; Mason, B.W.
Highlights: Notification letters were sent to 2781 patients deemed at risk of hospital-acquired Mycobacterium chimaera infection. The patient notification exercise helpline received 422 calls in total. Of 324 individual patient callers, 300 (92.6%) were referred on for clinical assessment.